Semiotic Analysis of Political Symbolism in Shi Lifeng's 'The Puppet Player' - Hikmatyar, Aditya Aditama Putri; Fadhiilah, Harun (Universitas Ciputra, 2025)
This study explores how Shi Lifeng’s painting The Puppet Player constructs and communicates political narratives through visual symbolism. Despite the frequent use of Mao Zedong’s imagery in Chinese contemporary art, limited research examines how Lifeng’s visual language functions as a political statement. Using Roland Barthes’ semiotic framework—denotation, connotation, and myth—this qualitative study analyzes color, spatial composition, object symbolism, and figure gestures in the artwork. The analysis reveals that dominant red hues, hierarchical composition, and theatrical staging signify ideological control and social struggle. These visual strategies expose how authority and manipulation are normalized through aesthetic codes. The findings highlight Lifeng’s critical stance toward power structures and his use of design principles to challenge political memory. This research contributes to the discourse of visual communication by demonstrating how semiotic analysis can decode layered meanings in politically charged imagery, offering insights for designers and researchers in understanding symbolism and narrative construction within visual art.